2005
DOI: 10.1111/j.1524-6175.2005.03869.x
|View full text |Cite
|
Sign up to set email alerts
|

Control of Blood Pressure and Other Cardiovascular Risk Factors at Different Practice Settings: Outcomes of Care Provided to Diabetic Women Compared to Men

Abstract: Cardiovascular disease (CVD) is the major cause of morbidity and mortality in diabetes. To determine the proportion of patients who met the5 were hypertension, hyperglycemia, increased low-density lipoprotein (LDL) cholesterol, low levels of high-density lipoprotein (HDL) cholesterol, and smoking. While tight control of blood glucose in both type 1 and type 2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
20
2

Year Published

2005
2005
2012
2012

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 41 publications
(44 reference statements)
4
20
2
Order By: Relevance
“…These data are consistent with two studies by our group involving various ethnic populations and demonstrating a high prevalence of obesity and dismal control of CVD risk factors among diabetes patients [5,6]. In our studies, less than 5% of diabetes patients achieved blood pressure, glycemic, and lipid control simultaneously [5,6].…”
Section: Introductionsupporting
confidence: 95%
“…These data are consistent with two studies by our group involving various ethnic populations and demonstrating a high prevalence of obesity and dismal control of CVD risk factors among diabetes patients [5,6]. In our studies, less than 5% of diabetes patients achieved blood pressure, glycemic, and lipid control simultaneously [5,6].…”
Section: Introductionsupporting
confidence: 95%
“…Previous studies have reported similar low percentage of patients achieving the combined ADA goals. 11,12 In the present study, optimal glycemic control was achieved by only one-third (34.4%) of the study population. Rest two-thirds of the patients had suboptimal control, out of which more than half were having very poor control with HbA1c of >9%.…”
Section: Discussionmentioning
confidence: 91%
“…10 The combined control of all the three target levels was achieved by even lesser percentage of patients. 11,12 Most studies that assessed the glycemic control of the subjects with diabetes did not look into the status of optimal control of comorbidities including dyslipidemia. 10 Moreover, the factors associated with DR in the group with suboptimal metabolic control have not been evaluated in population-based studies.…”
mentioning
confidence: 99%
“…Step 5: Measure Arterial Blood Pressure A large percentage of human type 2 diabetics are hypertensive, therefore control of blood pressure is essential to retard or prevent complications such as renal failure, retinopathy, or accelerated atherosclerosis (Bell et al 2005;Buch et al 2005;Cueto-Manzano et al 2005;McFarlane et al 2005;Teitelbaum et al 2005). Validated noninvasive methods for measuring blood pressure are available in several species (Krege et al 1995;Mesangeau et al 2000;Springett et al 2001).…”
Section: Criteria For Validating Models Of Type 2 Insulin-resistant Dmentioning
confidence: 98%